Studies in Intellectual History - Boas, George (Johns Hopkins University Press, 1953)
Originally published in 1953. In this collection of essays, prominent midcentury intellectual historians provide critical essays on their field of specialty. This volume gathers work by Harold Cherniss, George Boas, Ludwig Edelstein, Leo Spitzer, and others.